Integrasi Inovasi Digital dalam Manajemen Keuangan dan Rantai Pasok Industri Daur Ulang Plastik - Mahdi, Mahdi; Surya, Jen; Rahmi, Rahmi; Fahmi, Ijal; Shakira, Nadia (Jurnal Serambi Engineering, 2025)
The integration of digital innovation in the plastic recycling industry has become a strategic step to enhance efficiency, transparency, and competitiveness amid complex waste management challenges. This study employs a literature review approach to examine the potential implementation of digital technologies, including cloud-based financial systems, real-time logistics tracking, and e-wallet applications, to support financial management and distribution processes in the recycling sector. The findings indicate that digitalization has the potential to reduce operational costs by up to 25%, expedite financial reporting, and enhance investor confidence. Nevertheless, challenges persist, including inadequate digital literacy, deficient infrastructure, and resistance to change. The strategic recommendations encompass the provision of fiscal incentives, the implementation of continuous technical training, and the development of data-driven financing ecosystems. Digitalization has the potential to transform the plastic recycling industry by facilitating the transition to a more professional, inclusive, and sustainable system. This transition can be facilitated by collaborative support from government entities, industry leaders, fintech companies, and research institutions.